Functional Capabilities of Antonyms in the Russian Language - Марупов Шухрат Насимович; Усмонова Замира Ураловна (Scientific Trends, 2024)
According to some researchers: "Antonyms do not represent anything special, do not carry anything special in their content, while it is antonyms in their complete form that would help linguistics to explain much that has not yet been explained, especially since antonyms are hidden in words and phrases." It is stated that "The general understanding of antonyms and their assignment of units to each other, reflecting these meanings and giving clarity about their regularities, give linguistics all the grounds for their solution. The article will show how important antonyms are." The total number of antonyms, regardless of the parts of speech, is determined by the implication between antonymic words in the determinative model of the language, with the help of system-wide participation in the paradigmatic and syntagmatic opposition. The number of antonymic words is limited by the system-wide possibility of their coexistence in a determinative role in relation to the anisotropy of the linguistic subsystem under study.
Keywords: Linguistics, languages, terminology, antonym, complex grammar, vocabulary, linguistic terms